Maternal plasma vitamin D levels and associated determinants in late pregnancy in Harare, Zimbabwe: a cross-sectional study - Chikwati, Raylton P. (BMC Pregnancy Childbirth, 2019)
BACKGROUND: The importance of vitamin D in bone health and calcium homeostasis has been well documented. However, emerging evidence supports the role of vitamin D beyond its recognised traditional roles. In pregnancy, vitamin D levels are crucial in sustaining both the maternal stores and optimal growth of the foetus. In Southern Africa, there is paucity of data on vitamin D in pregnancy and related outcomes. To expand this body of knowledge, we assessed vitamin D levels in late pregnancy and (if any) associated maternal determinants in Harare, Zimbabwe. METHODS: Study participants comprised of 138 pregnant Zimbabwean women in their third trimester. These were stratified by HIV status; sampling median (IQR) gestation for HIV negative study participants was 34 weeks (26–41) and 31 weeks (20–40) in the HIV positive participants. Maternal plasma 25 hydroxyvitamin (OH) Dlevels were measured using the ClinPrepHigh Pressure Liquid Chromatography (HPLC) kit. Statistical analysis was carried out using the STATA statistical package version 13. A p-value of < 0.05was considered to be statistically significant. RESULTS: HIV infected participants had significantly higher mean 25 (OH) D concentration (112 ± 33.4 nmol/L) compared to the HIV uninfected (100 ± 27.1 nmol/L), p = 0.032.Participants whose samples were collected during summer had higher maternal 25 (OH) D levels than those cART duration and maternal 25 (OH) D levels (p = 0.031, Spearman correlation =0.28). CONCLUSIONS: Our findings show high mean levels of maternal 25 (OH) D in late pregnancy in our setting and in the absence of vitamin D supplementation. Both HIV infection and season are significant determinants of maternal vitamin D levels. Summer season is associated with higher maternal plasma 25 (OH) D levels. HIV infection is associated with increased maternal vitamin D levels. Prolonged use of cART, Tenolam E is associated with improved maternal 25(OH) D levels.